Original paperPHYSICAL FITNESS AND NUTRITIONAL STATUS OF POLISH GROUND FORCE UNIT RECRUITS - Tomczak, A.; Bertrandt, J.; Kłos, A. (Biology of Sport, 2012)
The purpose of the work was to conduct an examination of the physical fitness and nutritional status of recruits (221 men beginning military service in the infantry unit). Soldiers’ physical efficiency was estimated using 4 tests: standing long jump, pull-ups on bar, 30-second sit-ups and 1000-metre run. The nutritional status assessment was done based on anthropometric measurements including measurements of body height, body mass and selected skin fold thickness. The study group of soldiers were the best at sit-ups (46.33 points). They got over 40 points for the 1000-metre run (43.68 points) and for pull-ups on bar (41.69 points). They obtained the lowest scores for standing long jumps (30.77 points). About 14% of recruits were overweight and 4.1% underweight. Recruits enrolling in the infantry unit present a low physical fitness level. Overweight and obesity occurrence, and particularly underweight, in recruits testify to improper nutrition before beginning military service.